Coexistence of dipnech and carotid body paraganglioma: Is it just a coincidence? - Pedro, J (2020)
We describe the case of a 56 year-old woman with the almost simultaneous appearance of diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) and a carotid body paraganglioma. Of interest, 6 years earlier, the patient underwent total thyroidectomy due to papillary thyroid carcinoma and, in the meantime, she was submitted to mastectomy to treat an invasive ductal carcinoma of the breast. In order to explain these lesions, an extensive genetic study was performed. Results showed positivity for the presence of the tumor suppressor gene PALB2, whose presence had already been detected in a niece with breast cancer. The patient underwent different procedures to treat the lesions and currently she is symptom-free over 2 years of follow-up.